CLOUD TECHNOLOGIES IN THE DEVELOPMENT OF THE E-LERNING: THEORETICAL ASPECTS - Sazhko, H.; Pirsl, Danica S. (Problems of Engineer-Pedagogical Education, 2020)
This paper gives an overview of the current problems of the formation of cloud technologies based educational environment in the development of e-learning. The authors explore available theoretical developments in this area, consider methodological basis and technical options for the implementation of "cloud" based educational services. Nowadays it is difficult to argue that cloud-based technologies are incredibly in demand and are actively developing. A cloud computing technology refers to a technology that allows you to combine IT resources of various hardware platforms into a single whole and allows the user to access them via the Internet. Both positive and negative aspects of introducing cloud technologies into the educational process are examined from the technical, technological, didactic and economic view. Particular attention is paid to the topics that are directly included in the educational process or supporting its tasks, whose effectiveness can be increased if cloud services are introduced. In addition, several ways to implement this approach are proposed, based on the widespread cloud service delivery models. The paper also considers how cloud technologies provide the implementation of individual, group and collective forms of network interaction, the creation of a communication environment for the interaction of teachers and students in order to acquire new knowledge, control, evaluation and, in general, contribution to improving the level of professional training of various fields specialists. Analytical review allows the authors to formulate conclusions about the timeliness and need for research in the field of modern educational process, to identify the main prospects for the use of cloud technologies in professional activities The overview of the state of the problem of formation of educational environment based on cloud technologies in the development of e-learning is given in this paper. The authors explore the available theoretical developments in this area, consider methodological basis and technical options for the implementation of educational services based on the "cloud".